2005
DOI: 10.1111/j.1537-2995.2005.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus (HBV) DNA screening of blood donations in minipools with the COBAS AmpliScreen HBV test

Abstract: Implementation of HBV MP NAT will provide an increment in safety relative to HBV serologic screening, similar to that for HCV and in excess of that for HIV. Our data indicate that the implementation of HBV MP NAT would likely interdict 39 HBV window-period units and prevent 56 cases of transfusion-transmitted HBV infection annually. The current data indicate that HBV MP NAT should not lead to discontinuation of anti-HBc testing but that discontinuation of HBsAg testing with retention of anti-HBc testing may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 22 publications
2
118
2
Order By: Relevance
“…Therefore implementing a highly sensitive assay for HBV DNA screening in Lebanese blood donors, should be considered to avoid any false negative results. Previous studies have shown that various NAT commercial assays differ in their sensitivity (36)(37)(38), this could be associated with various factors such Hepat Mon. 2017; 17 (7):e14250.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore implementing a highly sensitive assay for HBV DNA screening in Lebanese blood donors, should be considered to avoid any false negative results. Previous studies have shown that various NAT commercial assays differ in their sensitivity (36)(37)(38), this could be associated with various factors such Hepat Mon. 2017; 17 (7):e14250.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of OHB among HBsAg-negative donors varies in different parts of the world, and as mentioned above, depends on the endemicity of HBsAg carriers as well as the method used to test the virus. Reports from subsets of donors from North America and Western Europe have ranged from as low as 0 % (presence of anti-HBc) (10,11) to as high as 2.8 % (isolated anti-HBc) (12,13). Similarly, studies from Asia (especially from highly endemic regions) have indicated prevalence rates of HBV-DNAHBV DNA detection among blood donors ranging from 0.…”
Section: Transfusion Settingsmentioning
confidence: 99%
“…to the values predicted by incidence/window model. A 24-sample minipool NAT for HBV showed a yield of 1 : 352.451 over routine serologic screening, thus of a similar magnitude as HIV and HCV yield observed [93]. The downside of HBV NAT was small yield and cost-effectiveness in low prevalence areas, especially with minipool NAT, as well as the lack of sensitivity of even ID NAT to detect extremely sparse HBV DNA particles involved in transmission by transfusion.…”
Section: Discussionmentioning
confidence: 63%